(3GdMQcI GdcTajI ceONd ddJQHjI Ydi GdJfhY GdKbGai (B/ s - (3jGSQ eMeO eMeO eMeO ehSis; (3CHhGdfhQ eUHGM CHhGdfhQ (B: s; (3fLhi jhSa LeGd GdOjf (B: s ((3GdbGgQI (B: s (3jGSQ eMeO eMeO eMeO ehSi (B: s, 2020)
(3JgOa GdOQGSI Edi hVY JUhQ ebJQM dJWhjQ GdCfTWI GdcTajI HGdLGeYGJ GdeUQjI ai VhA CHYGO GdJQHjI Ydi GdJfhY GdKbGai(B: (3MjK JgJe GdJQHjI Ydi GdJfhY GdKbGai HEYOGO GdaQO djchf EfSGfG UGdMG eJeScG HghjJg GdKbGajI(B: (3h bGOQG (B{u(32013(B} (3ai GdhbJ PGJg (B- (3Ydi GdGfaJGM GdKbGai h GdJhGUd eY GdBNQjf(B: (3HeG jYhO HGdfaY Ydi faSg h hWfg h GdYGde HCSQg(B: (3h GSJNOeJ GdOQGSI GdGSJHjGf(B: (3h GdedGMXI(B: (3h GdebGHdI; h Pdc dLeY GdHjGfGJ ef GdYjfI GdJj JchfJ ef WdGH h WGdHGJ GdLGeYGJ GdeUQjI GdeTJQcjf ai fTGW GdLhGdI HGdLGeYI; eY ebGHdI HYV bGOI GdMQcI GdcTajI HeUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe CUhd GdJQHjIs
(3UOQ GjVG cbQU eOeLs
Keywords: -(3GdMQcI GdcTajIs; (3GdJQHjI Ydi GdJfhY GdKbGais; (3GdJfhY GdKbGais